Hepatitis C virus and host cell lipids: An intimate connection - Alvisi, Gualtiero; Madan Renes, Vanesa; Bartenschlager, Ralf (RNA biology, 2011)
Hepatitis C virus (HCV) is a major human pathogen, persistently infecting more than 170 million individuals worldwide. The recent establishment of fully permissive culture systems allowed unraveling the close link between host cell lipids and HCV, at each step of the viral replication cycle. HCV entry is triggered by the timely coordinated interaction of virus particles with cell surface receptors, including the low-density lipoprotein receptor. Viral RNA replication strictly depends on fatty acids and cholesterol biosynthesis. This process occurs on modified intracellular membranes, forming a membranous web. Their biogenesis is induced by the viral nonstructural proteins (NS) 4B and NS5A and requires the activity of cellular lipid kinases belonging to the phosphatidylinositol-4-kinase III family. A hallmark of HCV-induced membranes is thus the presence of phosphatidylinositol-4-phosphate (PI4P), which is synthesized by these kinases. Intriguingly, certain recently identified HCV dependency factors selectively bind to PI derivatives, suggesting a crucial role for PIPs in viral RNA replication and assembly. The latter occurs on the surface of lipid droplets and is tightly connected to the very low density lipoprotein pathway leading to the formation of unique lipoviro particles. Thus, HCV exploits lipid metabolism in many ways and may therefore serve as a model system to gain insights into membrane biogenesis, lipid droplet formation and lipid trafficking.